2018
DOI: 10.1039/c8ra00335a
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of thermotolerant yeastKluyveromyces marxianusin multiple inhibitors tolerance

Abstract: During pretreatment of lignocellulosic biomass, toxic compounds were released and inhibited the growth and fermentation of microorganisms. Here the global transcriptional response of K. marxianus to multiple inhibitors including acetic acid, phenols, furfural and HMF, at 42 C, was studied, via RNA-seq technology.Genes involved in the glycolysis pathway, fatty acid metabolism, ergosterol metabolism and vitamin B6 and B1 metabolic process were enriched in the down-regulated gene set, while genes involved in TCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 98 publications
(120 reference statements)
1
39
0
Order By: Relevance
“…Considering the synergistic effects of these inhibitors, the construction of a strain with tolerance to multiple inhibitors has an increased practical application value. In our previous study, the significant up-regulation of KmYME was detected in the presence of multiple inhibitors [13]. Here, its upregulation was confirmed in the presence of multiple inhibitors or each single kind of inhibitor (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Considering the synergistic effects of these inhibitors, the construction of a strain with tolerance to multiple inhibitors has an increased practical application value. In our previous study, the significant up-regulation of KmYME was detected in the presence of multiple inhibitors [13]. Here, its upregulation was confirmed in the presence of multiple inhibitors or each single kind of inhibitor (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…In our previous study, the expression of an uncharacterized α/β-hydrolase domain (ABHD)-containing gene (GenBank BAP69980, locus tag KMAR_10772) of K. marxianus was significantly up-regulated in the presence of inhibitors derived from the pretreatment of lignocellulosic biomass [13]. In this study, after the up-regulation of its expression was confirmed through real time PCR, this gene was disrupted or overexpressed to evaluate its effect on tolerance to inhibitors.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations